Second Generation Nanoporous Silicon Nitride Membranes for High Toxin Clearance and Small Format Hemodialysis. Issue 4 (15th January 2020) - Hill, Kayli; Walker, Samuel N.; Salminen, Alec; Chung, Hung L.; Li, Xunzhi; Ezzat, Bahie; Miller, Joshua J.; DesOrmeaux, Jon‐Paul S.; Zhang, Jingkai; Hayden, Andrew; Burgin, Tucker; Piraino, Lindsay; et al.
Abstract: Conventional hemodialysis (HD) uses floor‐standing instruments and bulky dialysis cartridges containing ≈2 m 2 of 10 micrometer thick, tortuous‐path membranes. Portable and wearable HD systems can improve outcomes for patients with end‐stage renal disease by facilitating more frequent, longer dialysis at home, providing more physiological toxin clearance. Developing devices with these benefits requires highly efficient membranes to clear clinically relevant toxins in small formats. Here, the ability of ultrathin (<100 nm) silicon‐nitride‐based membranes to reduce the membrane area required to clear toxins by orders of magnitude is shown. Advanced fabrication methods are introduced that produce nanoporous silicon nitride membranes (NPN‐O) that are two times stronger than the original nanoporous nitride materials (NPN) and feature pore sizes appropriate for middle‐weight serum toxin removal. Single‐pass benchtop studies with NPN‐O (1.4 mm 2 ) demonstrate the extraordinary clearance potential of these membranes (10 5 mL min −1 m −2 ), and their intrinsic hemocompatibility. Results of benchtop studies with nanomembranes, and 4 h dialysis of uremic rats, indicate that NPN‐O can reduce the membrane area required for hemodialysis by two orders of magnitude, suggesting the performance and robustness needed to enable small‐format hemodialysis, a milestone in the development of small‐format hemodialysis systems. Abstract : Portable, wearable, and implantable hemodialysis (HD) systems require highly efficient membranes that enable clinically relevant toxin removal. Benchtop studies with chip‐based membranes and 4 h dialysis of uremic rats, demonstrate the clearance potential (10 5 mL min −1 m −2 ) of small format hemodialysis devices.